Diario de José Donoso: de la pose y del doble - Morales, Leonidas (Revista Chilena de Literatura, 2014)
The critical work of this article encompasses a textual corpus built around José Donoso’s unpublished Diario. Considering this corpus and the complex issues it displays, the study focuses on two main themes: pretense and the double. Pretense leads us into a theory of narrative truth that ensues as a result of artfulness. In turn, the double and its roots in a fixation with narcissism reveal a genealogy of characters that also remain divided in Donoso’s novels.